Effect of Vitamin D deficiency on asthma among children in Saudi Arabia - ALshahrani Mohamad Ali A (South Eastern European Journal of Public Health, 2025)
Asthma is a prevalent condition, impacting over 300 million individuals and their families. Genetic predisposition, early allergen exposure, infections, food, tobacco smoke exposure, pollution, and vitamin D levels are all suggested to affect the onset and severity of asthma. This study aims to ascertain the effect of vitamin D deficiency on asthma among Saudi children. A cross-sectional study was performed in the several government hospitals in Asir region, such as Asir Central Hospital, Khamis Mushayt Civil Hospital, Ayha Women, Maternity and Children Hospital, and Khamis Women, Maternity and Children Hospital. The serum 25-hydroxyvitamin D concentration was measured in children aged 1 to 14 years diagnosed with bronchial asthma (ages 6 to 14) or recurrent wheezing episodes (under 6 years). The severity of asthma was assessed using the Global Initiative for Asthma evaluation, the Asthma Control Test, and the Childhood Asthma Control Test. Demographic and clinical data were examined between patients with low and normal 25-OH vitamin D levels, and the relationship between asthma severity and 25-OH vitamin D levels was evaluated. Among the 400 children studied, 25-OH vitamin D levels were deficient in 240 (60%) and insufficient in 120 (30%) children. Only 40 children (10%) exhibited adequate levels of 25-OH vitamin D. A notable link exists between the severity of asthma symptoms and 25-OH vitamin D insufficiency.